Corrosion engineering on AlCoCrFeNi high-entropy alloys toward highly efficient electrocatalysts for the oxygen evolution of alkaline seawater - Chen, Zhibin (2024)
Seawater splitting is a prospective approach to yield renewable and sustainable hydrogen energy. Complex preparation processes and poor repeatability are currently considered to be an insuperable impediment to the promotion of the large-scale production and application of electrocatalysts. Avoiding the use of intricate instruments, corrosion engineering is an intriguing strategy to reduce the cost and presents considerable potential for electrodes with catalytic performance. An anode comprising quinary AlCoCrFeNi layered double hydroxides uniformly decorated on an AlCoCrFeNi high-entropy alloy is proposed in this paper via a one-step corrosion engineering method, which directly serves as a remarkably active catalyst for boosting the oxygen evolution reaction (OER) in alkaline seawater. Notably, the best-performing catalyst exhibited oxygen evolution reaction activity with overpotential values of 272.3 and 332 mV to achieve the current densities of 10 and 100 mA·cm−2, respectively. The failure mechanism of the obtained catalyst was identified for advancing the development of multicomponent catalysts.